2016
DOI: 10.1371/journal.pone.0165312
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Transcriptomic Responses of Full-Thickness Dermal Excision Wounds to Pseudomonas aeruginosa Acute and Biofilm Infection

Abstract: Pseudomonas aeruginosa infections of wounds in clinical settings are major complications whose outcomes are influenced by host responses that are not completely understood. Herein we evaluated transcriptomic changes of wounds as they counter P. aeruginosa infection—first active infection, and then chronic biofilm infection. We used the dermal full-thickness, rabbit ear excisional wound model. We studied the wound response: towards acute infection at 2, 6, and 24 hrs after inoculating 106 bacteria into day-3 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…1 . Our previous report describes the transcriptomic response of the rabbit ear wound tissue to this infection as well as the P. aeruginosa viable counts and morphology at each post-infection timepoint, including biofilm morphology characterized as aggregates on Days 5 and 9 that was confirmed by gene expression 21 .
Figure 1 Study design .
…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…1 . Our previous report describes the transcriptomic response of the rabbit ear wound tissue to this infection as well as the P. aeruginosa viable counts and morphology at each post-infection timepoint, including biofilm morphology characterized as aggregates on Days 5 and 9 that was confirmed by gene expression 21 .
Figure 1 Study design .
…”
Section: Resultsmentioning
confidence: 97%
“…After residing in the wounds for 24 h, the PAO1 inoculum increased in viable counts by 2 logs 21 . Coincidently, the COGs related to elevated metabolism and cell replication that were down-regulated at 2 h became mostly up-regulated after 24 h in the wound (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the application of omics technologies, we have gained insight into P. aeruginosa ’s genome organisation and diversity 8 , 10 , 11 , 22 , 100 , habitat-specific transcriptome 101 105 , proteome 106 108 , and metabolome 108 112 and the co-evolution of P. aeruginosa with competitors in human habitats such as Staphylococcus aureus 113 115 . The function of hundreds of previously uncharacterised “conserved hypotheticals” 11 and the structure of secretory nanomachines have been resolved 37 , 41 , 116 121 and knowledge has been gained about the complex regulation of the release of exopolysaccharides, secondary metabolites, and virulence effectors 1 .…”
Section: Looking Back Forwardmentioning
confidence: 99%
“…Wound repair can also be assessed using more physiological models by performing wounds (of determined diameters), ex vivo , on explanted epithelial tissues, as well as in vivo , on live animals. It has been shown that P. aeruginosa laboratory or clinical strains decrease the repair rate of cutaneous wounds in rabbit, murine or porcine in in vivo models (Zhao et al, 2010; Mendes et al, 2013; Pastar et al, 2013; Brandenburg et al, 2015; Karna et al, 2016; Chaney et al, 2017). Conversely, Gao et al observed that purified P. aeruginosa flagellin significantly accelerated the wound closure of porcine eye wounds (Gao et al, 2010).…”
Section: Evidence For Epithelial Repair Impairment By Pseudomonas Aermentioning
confidence: 99%